Relationship between eating habits and involvement in physical activity among male and female physical and Health Education's students / Rockye Vun Sang - Vun Sang, Rockye (Faculty of Education, 2014)
Poor nutritional practices and heightened levels of stress, two common attributes of university life, are strongly linked with weight gain and decreased health. One study was conducted among male and female students of Physical and Health Education students, Faculty of Education, UiTM Shah Alam. This study to determine the relationships university students' eating habits and involvement in physical activity between male and female. As much as 30 packs questionnaire form was distributed to all Physical and Health Education students. Questionnaire divided 15 questions for male and 15 female students to more validity and also contains three sections which part constitutes questions of demographic, eating habits and physical activity and lifestyle. The results shown the gender was not influences to the lifestyles and eating behavior along with the relationships do exists between lifestyles and campus eating behavior.